2019
DOI: 10.11604/pamj.supp.2019.32.1.13352
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of suspected pertussis in Kaltungo, Gombe State, Northern Nigeria, 2015: the role of sub-optimum routine immunization coverage

Abstract: Introduction Despite the availability of vaccines, pertussis outbreaks still occur in developing countries. In December 2015 we investigated a pertussis outbreak in Kaltungo, Nigeria to identify determinants of infection and institute control measures. Methods We enrolled 155 cases and 310 unmatched controls. We defined cases as residents of Kaltungo with paroxysmal or whooping cough lasting 2 weeks with or without vomiting and randomly selected neighborhood controls. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
2
13
1
Order By: Relevance
“…Regarding the overall case fatality rate, our study found a much lower case fatality rate than the previous studies conducted in Gombe State, Northeastern Nigeria, and Ethiopia. 12,13,15 However, our study finding is comparable to a study published in 2009 from Argentina where case fatality rate was 0.17% based on analyzed outbreaks data. 19 Furthermore, we found a sex difference in case fatality rate, suggesting that males are more likely to die of pertussis when infected than females.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the overall case fatality rate, our study found a much lower case fatality rate than the previous studies conducted in Gombe State, Northeastern Nigeria, and Ethiopia. 12,13,15 However, our study finding is comparable to a study published in 2009 from Argentina where case fatality rate was 0.17% based on analyzed outbreaks data. 19 Furthermore, we found a sex difference in case fatality rate, suggesting that males are more likely to die of pertussis when infected than females.…”
Section: Discussionsupporting
confidence: 87%
“…Our result is not different from previous studies that reported the protective effect of full vaccination against pertussis. 13,15…”
Section: Discussionmentioning
confidence: 99%
“…There were five studies which reported epidemiology data for pertussis in Africa, namely Senegal [ 27 ], Tunisia [ 28 ], Algeria [ 29 ], Nigeria [ 30 ], and Uganda [ 31 ], and seven studies which reported sero-epidemiology in Senegal [ 32 ], Cameroon [ 33 ], South Africa [ 34 ], Tunisia [ 35 , 36 ], Morocco [ 37 , 38 ], and Gambia [ 39 ]. There were seven studies with mortality data including Nigeria [ 30 , 40 ], Ethiopia [ 41 ], Morocco [ 42 ], South Africa [ 43 , 44 ], and Senegal [ 27 ].…”
Section: Search Resultsmentioning
confidence: 99%
“…In Nigeria, based on a clinical definition, and a population of 155 young children and adolescents of undefined age (5 cases in children aged 10–14 years) [ 30 ], the overall pertussis attack rate of suspected cases was 155/11,172 (1.4%), and the CFR was 24/155 (15.5%). The authors noted that the CFR was highest in those aged 12–59 months.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation